MiR-548ar-3p increases cigarette smoke extract-induced chronic obstructive pulmonary disease (COPD) injury through solute carrier family 17 member 9 (SLC17A9) - Zhang, Longju; Liu, Xiaoli; Zheng, Yi; Du, Fei; He, Gang (Archives of Biological Sciences, 2022)
Paper description: The pathogenesis of chronic obstructive pulmonary disease (COPD) caused by smoking is unclear. miR-548ar-3p was selected by high-throughput sequencing of peripheral blood from smoking (COPD) and non-smoking (normal) individuals. A miR-548ar-3p mimic was transfected into human bronchial epithelial (HBE) cells and a COPD model was established by treating HBE cells with cigarette smoke extract (CSE). The effect of miR-548ar-3p on cell proliferation, apoptosis and SLC17A9 protein expression was examined. miR-548ar-3p was expressed at a lower level in COPD patients. It caused decreased cell viablity, promoted apoptosis and increased SLC17A9 protein expression. miR-548ar-3p may aggravate CSE-induced COPD injury through SLC17A9. Abstract: This study investigated the effect of microRNA mir-548ar-3p on cigarette smoke extract (CSE)-induced chronic obstructive pulmonary disease (COPD). High-throughput sequencing was performed on peripheral blood from smoking COPD patients and non-smoking individuals with normal pulmonary function, and miR-548ar-3p RNA, possessing large differential expression was selected. Experimental groups were divided into control, experimental model (EM), EM+mimic miRNA, negative control (NC) and EM+miR-548ar-3p groups; an empty vector or miR-548ar-3p mimic was transfected into human bronchial epithelial (HBE) cells. A COPD model was established by treating HBE cells with CSE. Cell viability, apoptosis and solute carrier family 17 member 9 (SLC17A9) protein expression were examined by cell counting kit-8, flow cytometry and Western blotting, respectively. Cell viability in the EM+miR-548ar-3p group decreased significantly, and the apoptosis rate and SLC17A9 protein expression increased significantly compared with the control (P<0.05, all groups). In smoking COPD patients, interferon (IFN)-γ and interleukin (IL)-17α expression detected by ELISA was significantly higher than in normal individuals. miR-548ar-3p expression was significantly lower (P<0.05, all groups). These findings suggest that miR-548ar-3p was expressed at a lower level in COPD patients. miR-548ar-3p may increase the extent of CSE-induced COPD injury through SLC17A9